Associations of students’ linguistic distance to the language of instruction and classroom composition with English reading and listening skills - Jaekel, Nils; Ritter, Markus; Jaekel, Julia (Studies in second language acquisition, 2023)
Globally classrooms are increasingly linguistically diverse. Research often oversimplifies lived linguistic heterogeneity as binary variables: native versus non-native. Linguistic distance (LD) measures allow a fine-grained operationalization of linguistic diversity in foreign language education. This study investigated associations of cognate LDs of students’ home languages and classroom heterogeneity with English as a Foreign Language skills. Data were collected from a diverse sample of 5,130 Year 5 students in Germany. Mixed-effects linear models confirmed our hypotheses that higher individual LDs and a higher proportion of multilingual learners per classroom were both independently associated with lower English proficiency. Multilingual learners with higher cognate LDs to English and students in more linguistically heterogeneous classrooms had lower English proficiency. The results emphasize the need to assess LD in research to better differentiate between students. Foreign language classrooms seem not to address linguistic diversity adequately and need to readjust their focus to better meet multilingual learners’ needs.